Systematic review of the association between Alzheimer’s disease and chronic glaucoma - Janssen SF (Dove Medical Press, 2015)
Sarah F Janssen,1 Nomdo M Jansonius,2 Femke Bouwman,3 Frank D Verbraak,1,4 Arthur A Bergen51Department of Ophthalmology, VU Medical Center, Amsterdam; 2Department of Ophthalmology, University of Groningen, University Medical Center Groningen, Groningen; 3Alzheimer Center, VU Medical Center, 4Department of Ophthalmology, 5Department of Clinical Genetics, Academic Medical Center, Amsterdam, the NetherlandsWe read with great interest the paper by Tsilis et al entitled "Systematic review of the association between Alzheimer’s disease and chronic glaucoma" published recently in this journal.1 The potential overlap in the pathobiological background of Alzheimer’s disease (AD) and primary open angle glaucoma (POAG) is currently a topic of intense discussion and could provide further insight into both of these complex diseases.View original paper by Tsilis et al.